Acompanhamento da vida útil de tilápias (Oreochromis niloticus) mantidas em gelo, através de abordagem de variáveis microbiológicas, químicas e sensoriais - Costa, Jéssica Frota (2019)
Determination of parameters that can be used as universal quality indicators of a task involving once for all fish species, nutritional quality, safety, food supply and characteristics of the species analyzed. The report of general and periodic changes in the monitoring of Nile tilapia (Oreochromis niloticus) in the selective monitoring of multivariate sensorial, bacterial and chemicals. For the experiment, the fish were kept with ice (0ºC) in isothermal boxes, without being replenished or removed, and inside the refrigerator with a controlled temperature of 2ºC. From day zero, and every 7 days, a fish was removed for the sensorial, microbiological and physico-chemical analyzes until the twenty-eighth day (T0 to T28). The used ice was also analyzed microbiologically. In each fish, the quality index (QIM), attributes of mesophilic and psychrophilic heterotrophic bacterial groups, total nitrogenous volatile bases (N-BVT) and hydrogenation potential (pH) of the muscle were determined. Isolates and purification of bacteria grown in the culture media for taxonomic identification were made. Pearson's linear correlation analysis was applied to the data concerning the bacterial counts and attributes considered in the QIM. In sensory analysis, the average score of the panelists ranged from 0.5 to 15.25. Individually the "general appearance" attribute reached the highest score in T28, and the attribute eyes, which presented the highest score in T7 and T14. The commercial ice sample used did not present contamination by thermotolerant coliforms being in accordance with the recommended by the current legislation. There was a high positive correlation between bacterial counts / QIM attributes and bacterial / N-BVT counts. The variation of BVT was from 0.84 to 20.08 N / 100g, remaining within acceptable for human consumption. The pH values ranged from 6.32 to 6.94, disregarding the maximum limit recommended by Brazilian legislation. The main bacterial genera identified in the samples were: Pseudomonas, Bacillus, Staphylococcus, Micrococcus, Aeromonas, Citrobacter, and Enterobacter with predominance of Gram positive bacteria. With the application of QIM in fish quality evaluation it was possible to verify that changes in attributes related to fish quality were only perceptible to the panelists from the seventh day of storage, which coincided with the increase in the number of mesophilic bacteria and the detection of psychophilic bacteria in fish muscle. For the specie analyzed, the N-BVT showed to be a low efficiency parameter in the indication of fish quality while the pH values were consistent with the sensorial and microbiological parameters.